Feedback Control of Rijke-Type Thermo-Acoustic Instability. Issue 4 (December 2014) - Zhang, Zhiguo; Guan, Di
Thermo-acoustic instabilities are characterized by large-amplitude pressure oscillations, which are detrimental to land-based gas turbine and aero-engines. In this work, a real-time monitoring and feedback control strategy is developed, which involves two algorithms. One is an identification algorithm, which is used to 'sense' the condition of a combustion system and to conduct system identification. The algorithm performs somewhat similar to short-time Fourier transform, but is suitable for real-time computation and is able to more accurately estimate frequency using a shorter sample length. Furthermore it can output a reconstructed signal whose frequency is twice of the input signal, which has great potential to be used for system identification. The other algorithm is a revised infinite impulse response (IIR) filter; its efficiency is optimized by using LMS (least mean square). Finally, the control strategy is then experimentally implemented on a Rijke tube. It is found that approximately 50 dB sound reduction is achieved by actuating a loudspeaker. In addition, the control strategy is demonstrated to be able to track and prevent the onset of new limit cycle results from changes of fuel flow rate.